Worker Protection Standard: Notification and Hazard Communication - Frederick M. Fishel; Tatiana Sanchez (EDIS, 2016)
The Worker Protection Standard (WPS) is a Federal regulation designed to protect agricultural workers (people involved in the production of agricultural plants) and pesticide handlers (people mixing, loading, or applying pesticides or doing other tasks involving direct contact with pesticides). It has been in full implementation since 1995. This 3-page document provides general guidance to help you comply with the requirements of the Federal Worker Protection Standard (WPS) for agricultural pesticides, 40 CFR part 170, as amended in 2015. It also addresses notifying workers of pesticide applications on agricultural establishments. Written by Frederick M. Fishel and Tatiana Sanchez, and published by the Agronomy Department, October 2016.